The genus Adiantum in the state of Parana, Brazil - Brozoski, Ana Lucia (2023)
The genus Adiantum in the state of Parana, Brazil. We present the taxonomic treatment of the genus Adiantum (Pteridaceae) in the state of Paraná, Brazil. Adiantum has approximately 200 species in the Neotropics, of which 65 to 70 occur in South America and 64 in Brazil. The genus can be recognized by presenting marginal sori, with the margin of the lamina becoming revolute to form a pseudo-indusium. This study is based on the observation of approximately 214 specimens, mainly from Herbaria in Paraná and images available in online databases. Fifteen species were recorded for the state, the vast majority occurring in the Atlantic Forest of Serra do Mar. Among these species, five are endemic to Brazil, and ten are widely distributed in the Neotropics. Although no species are endemic to Paraná, some are rare in the state, deserving special attention regarding their conservation. We present morphological descriptions, identification keys, as well as comments on each of the species and their affinities, distribution maps, as well as illustrations to facilitate the identification of each species.